Assessment of Antibiotic Resistance Profile in Uropathogenic E. coli Isolates from Clinically Presumed UTI Patients in Telangana - Kiran, Suripeddi Ravi; Rahul, Gujjula; Devi, Jammula Achyutha (Asian Journal of Biological and Life Sciences, 2026)
Purpose: The purpose of the current investigation is to assess the antibiotic susceptibility pattern of Escherichia coli (E. coli) isolated from urine samples of patients suspected of having UTIs. The majority among them tested positive for E. coli in the culture. Results: The Minimum inhibitory concentration of Trimethoprim/Sulfamethoxazole was highest and that of Ciprofloxacin was the least for E. coli. The isolated samples showed the highest level of resistance towards Ampicillin (22%), followed by Nalidixic Acid (20%), Ciprofloxacin (20%), Cefuroxime (18%), Cefuroxime axetil (18%), and Ceftriaxone (17%). The demographic statistical data show that women prone more to UTIs with a higher incidence at 21-30 years age group. Significant colony growth in different age groups in In-patient samples showing was observed. The β-lactamase-producing E. coli were high in both in-patient and out-patient urine samples. The nitrite test and distribution of pus cells confirmed the presence of UTI in most samples. Further, higher amounts of CTX-M type of Extended-spectrum β-lactamase producing E. coli were observed in urine samples of in-patients that unequivocally show the organism's resistance to different classes of antibiotic drugs. Conclusion: The results indicate that most cases of UTIs were caused in females which were mostly because of the multidrug-resistant E. coli.
Keywords: β-lactamase; Escherichia coli; Multi-Drug Resistance; Urinary tract infection